Current situation of karst groundwater environmental problems and spring source protection in the Gudui-Nanliang spring basin - Zhiheng Wang; Yongping Liang; Zheming Shi; Haoyong Shen; Songtao Zhang; Yi Zhao; Hao Xie; Chunhong Zhao; Chunlei Tang (地质科技通报, 2023)
Objective The Gudui-Nanliang spring basin located in southern Shanxi Province is a complex karst water system with the coexistence of deep and shallow circulation, the transformation of cold and hot water, and multistage discharge. Due to long-term unreasonable exploitation and utilization, a series of geological environment problems related to karst groundwater have emerged in the spring basin. The present study aims to propose an ecological restoration and planning scheme for the spring basin by discussing in detail the status of karst groundwater-related environmental problems and their causes. Methods Based on a hydrogeological survey, this paper comprehensively employs a variety of methods, including comparative analysis of groundwater flow field, hydrogeochemical and isotopic analysis, and evaluation of karst water resources. Results The results show that due to the superimposed effects of climate change and human activities, Gudui Spring, Nanliang spring, and Haitou spring cut off the flow in 1999, 1992, and 2002, respectively, and the average decline rate of the regional groundwater level from 2013 to 2021 reaches 2.53 m/a. The results of hydrochemical and isotopic analysis indicate that the recharge to the karst groundwater of porous groundwater from unconsolidated deposits through leakage and surface water from Sanquan Reservoir through seepage cannot be ignored. The proportion of karst water samples worse than the water quality standard of class Ⅲ in the spring basin increased from 62.5% in 2014 to 81.25% in 2021. The range of 0.904 km2 of the spring source area can be subdivided into core protection zone, general protection zone and reservoir storage zone. Ecological protection and restoration planning should be carried out considering the differences between the three zones. Conclusion The results of the study can provide a basis for the comprehensive management of groundwater overexploitation areas in Shanxi Province and the ecological restoration and protection of Gudui spring basin.